Studi Validasi Autopsi Verbal Kematian Bayi - Ernaningsih Siswanto Agus Wilopo, Djauhar Ismail (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Infant mortality is a tragedy which cannot be easily forgotten by mothers and their family. Data on mortality from hospital or hospital-based cause of death was not representative. Community-based cause of death with verbal autopsy approach is a way to provide statistical data on mortality. Personnel of verbal autopsy are medical staff or skilled non-medical staff. Limited number of medical staff and midwifes has made all verbal autopsy processes impossible to be carried out by medical staff. Therefore a method of verbal autopsy needs to be developed by non medical staff. This method should be validated prior to its implementation.Objectives: The objective of the study was to identify verbal autopsy validity viewed from measurement process conducted by different measurement staff to reach final diagnose agreement on cause of infant mortality between medical and non medical staff compared to doctor’s diagnose as gold standard.Methods: The study used a diagnostic test with retrospective cohort research design. Numbers of samples were 110 cases and length of study was 3 months. Cases were taken from infant mortality which occurred in hospitals during the last 3 years with their medical records. Training was given for 1 / day to midwives and statistic officers on how to execute verbal autopsy. Questionnaires used were adapted from World Health Organization which had been translated and tested in on settings. Staff conducted measurement or interview with statistic officers and a week later with midwives.Results: Analysis result of Kappa statistical test showed that value of agreement between doctor’s diagnose and verbal autopsy by statistic officers was 0.57 with p=0.00. This meant that there was good agreement. Result of Kappa statistical test between midwifes and statistic officers was 0.63 with p=0.000. This also showed good agreement between midwife verbal autopsy and statistic officer verbal autopsy. Statistic officers could conduct verbal autopsy.Conclusion: Agreement reached between statistic officers and doctors diagnose was quite good. Statistic officers could conduct verbal autopsy.Keywords: verbal autopsy, validation, infant mortality